Rapid synthesis of fluorescent single-chain nanoparticles via photoinduced step-growth polymerization of pendant carbazole units - Kilic, Deniz; Pamukcu, Ceren; Balta, Demet Karaca; Temel, Binnur Aydogan; Temel, Gokhan (PERGAMON-ELSEVIER SCIENCE LTD, 2020)
An easy and rapid strategy is developed to synthesize light responsive single-chain nanoparticles via photo induced radical coupling of carbazole moieties in the side chain of polymer. Firstly, nitroxide-mediated radical polymerization is carried out for the synthesis of chloride functional styrenic copolymer. Pendant chloride groups of the polystyrene copolymer are converted to carbazole units by one-step modification. Constructed functional polymer undergoes photochemically intramolecular crosslinking using carbazole step-growth polymerization. Size of the nanoparticles can be manipulated by changing the degree of polymerization which is dependent to the dose of UV exposure. Achieved single-chain nanoparticles exhibit higher glass transition temperatures and lower hydrodynamic radii compared to their linear analogue. Polymeric nanoparticles are successfully employed for the cyclohexane oxide polymerization as cationic photoinitiators in the presence of an iodonium salt.
Keywords: Single-chain nanoparticles; Carbazole; Polymeric nanoparticles; Step-growth; Photoinduced crosslinking; CROSS-LINKING; STRATEGY; Polymer Science